Distinct Analgesic Actions of DHA and DHA-Derived Specialized Pro-Resolving Mediators on Post-operative Pain After Bone Fracture in Mice - Zhang, Linlin; Terrando, Niccolò; Xu, Zhen-Zhong; Bang, Sangsu; Jordt, Sven-Eric; Maixner, William; Serhan, Charles N.; Ji, Ru-Rong (Frontiers in Pharmacology, 2018)
Mechanisms of pain resolution are largely unclear. Increasing evidence suggests that specialized pro-resolving mediators (SPMs), derived from fish oil DHA (docosahexaenoic acid), promote the resolution of acute inflammation and potently inhibit inflammatory and neuropathic pain. In this study we examined the analgesic impact of DHA and DHA-derived SPMs in a mouse model of postoperative pain induced by tibial bone fracture (fPOP). Intravenous perioperative treatment with DHA (500 g), resolvin D1 (RvD1, 500 ng) and maresin 1 (MaR1, 500 ng), 10 min and 24 h after the surgery, delayed the development of fPOP (mechanical allodynia and cold allodynia). In contrast, post-operative intrathecal administration of DHA (500 g) 2 weeks after the surgery had no effects on established mechanical and cold allodynia. However, by direct comparison intrathecal post-operative treatment (500 ng) with neuroprotectin D1 (NPD1), MaR1 and D-resolvins, RvD1 and RvD5, but not RvD3 and RvD4, effectively reduced mechanical and cold allodynia. ELISA analysis showed that perioperative DHA-treatment increased RvD1 levels in serum and spinal cord samples after bone fracture. Interestingly, sham surgery resulted in transient allodynia and increased RvD1 levels, suggesting a correlation of enhanced SPM levels with acute pain resolution after sham surgery. Our findings suggest that 1) perioperative treatment with DHA is effective in preventing and delaying the development of fPOP, and 2) post-treatment with some SPMs can attenuate established fPOP. Our data also indicate that orthopedic surgery impairs SPM production. Thus, DHA and DHA-derived SPMs should be differentially supplemented for treating fPOP and improving recovery.